Integration of Luenberger estimator with control reconfiguration system for hypersonic aircraft - Zaludin, Zairil (IEEE, 2023)
Dynamic instability of hypersonic aircraft was well known. To ensure a stable and controlled flight throughout the hypersonic flight phase, a robust automatic flight control system was needed. In addition, in the unlikely event of a flight control failure, the autopilot must be able to remain operational and maintain flight stability. In this paper, the hypersonic aircraft feedback control system was designed using Linear Quadratic Regulator theory to guarantee dynamic stability and ensure robustness. Not all aircraft state variables were measurable hence, Luenberger estimator was incorporated to estimate the other states. Then a Control Reconfiguration System was incorporated to recover dynamic stability in the event of flight control failure. The work done showed that during single flight control malfunction, the feedback control system, Luenberger estimator and Control Reconfiguration System were able to maintain flight stability. This paper also shows that activities of the remaining working flight controls increased significantly to compensate for the lost, to maintain dynamic stability.